The Impact of COVID-19 On Migration Versus The Impact of The Financial Crisis on Migration - Elena F. MATEI; Ioana M. MINDRICAN (Communications of International Proceedings, 2021)
The onset of a global crisis is a negative macroeconomic phenomenon regardless of the reason for its onset. Both the emergence of the financial crisis in 2008 and the health crisis in 2020 led to the impact of the migration phenomenon and thus the standard of living of the population. The purpose of this paper is to analyze and study the evolution of immigrants and emigrants in the context of the onset of the financial crisis in 2008 compared to the onset of the health crisis generated by COVID-19. The analysis focuses on changes in Romania, Poland and Hungary because these countries have a similar economic structure, practice the floating exchange rate regime and are states with a derogation from the adoption of the single currency. Compared to the way of presenting the information from the selected bibliography, in this paper are found only the essential aspects, the particularities of the chosen research topic, which finally provides an overview.
Keywords: Crisis; Covid-19; Measures; Evolution